Rice Stripe Mosaic Disease: Characteristics and Control Strategies - Wang, Zhiyi; Chen, Biao; Zhang, Tong; Zhou, Guohui; Yang, Xin (Frontiers in Microbiology, 2021)
Rice stripe mosaic disease (RSMD) is caused by the rice stripe mosaic virus (RSMV; genus Cytorhabdovirus, family Rhabdoviridae). In recent years, significant progress has been made in understanding several aspects of the disease, especially its geographical distribution, symptoms, vectors, gene functions, and control measures. Since RSMD was first detected in southern China in 2015, it has been found in more and more rice growing areas and has become one of the most important rice diseases in southern China. RSMV is transmitted by the leafhopper Recilia dorsalis in a persistent-propagative manner, inducing yellow stripes, a slight distortion of leaves, increased tillers, and empty grains in rice plants. The virus has a negative-sense single-strand RNA genome of about 12.7 kb that encodes seven proteins: N, P, P3, M, G, P6, and L. Several molecular and serological tests have been developed to detect RSMV in plants and insects. The disease cycle can be described as follows: RSMV and its vector overwinter in infected plants; viruliferous R. dorsalis adults transmit the virus to spring rice and lay eggs on the infected seedlings; the next generation of R. dorsalis propagate on infected seedlings, become viruliferous, disperse, and cause new disease outbreaks. Control measures include monitoring and accurate forecasting, selecting disease-resistant varieties, improving cultivation systems, covering rice seedling nurseries with insect-proof nets, and using pesticides rationally. Inappropriate cultivation systems, pesticide overuse, and climatic conditions contribute to epidemics by affecting the development of vector insects and their population dynamics.